The Identity Construction of Jordanian Muslim Woman Reflected in Willow Trees Don’t Weep Novel (2014) by Fadia Faqir - Ida Rosida; Molalita Molalita (Insaniyat : Journal of Islam and Humanities, 2016)
This  article  discusses  the  identity  construction  of  a  Jordanian  Muslim  woman  through  the  main female character named Najwa reflected in Willow Trees Don’t Weep novel (2014) by Fadia Faqir. The method used in this study is descriptive qualitative. It is supported by the concept of identity by Stuart Hall and that of patriarchy to analyze the text. The aim of the study is to point out how Najwa, as a Jordanian Muslim woman who lives in a strong patriarchal culture without male figure in her family,  constructs  her  identity,  particularly  when  travelling  to  some  different  countries  including Pakistan, Afghanistan, and England just to find her father. The way Najwa Lives in a new country, where she interacts with new people and be immersed in new culture, has an immense impact on her.  Subsequently  self-identity  construction  is  definitely  inevitable.  Here,  Najwa  herself  strives  to negotiate  and  articulate  her  identity  through  her  appearance  and  behavior,  especially  in  Islamic practices and rituals. Consequently, the negotiation and articulation turn out to be the two major things  in  her  self-identity  construction.  Culture,  however,  becomes  a  crucial  mean  to  identity. Different culture represents different identity, and it keeps changing relaying on place where she lives.DOI: 10.15408/insaniyat.v1i1.4169